2020
DOI: 10.1177/0264550520939180
|View full text |Cite
|
Sign up to set email alerts
|

If you want to change the world you have to start with yourself: The impact of staff reflective practice within the Offender Personality Disorder pathway

Abstract: The offender personality disorder (OPD) pathway was implemented in 2012 to help improve services for people with personality difficulties within the criminal justice system. The OPD pathway acknowledges the importance of supervision, training and reflective practice for staff working with this client group and such activities have therefore been embedded within this initiative. Despite the research from this pathway identifying benefits to both staff and service users, there is a gap in knowledge about the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Again, in previous research, we found a high level of support for the provision of clinical supervision by staff working on the Offender Personality Disorder Programme. The OPD Pathway makes use of reflective practice sessions whereby staff meet -voluntarily -'to discuss team or individual issues; consider their emotional reactions, thoughts and ways in which they could adapt; and develop their clinical practice' (Webster et al, 2020). Importantly, Webster et al (2020: 290) suggest that reflective practice is a useful endeavour for people working in probation:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, in previous research, we found a high level of support for the provision of clinical supervision by staff working on the Offender Personality Disorder Programme. The OPD Pathway makes use of reflective practice sessions whereby staff meet -voluntarily -'to discuss team or individual issues; consider their emotional reactions, thoughts and ways in which they could adapt; and develop their clinical practice' (Webster et al, 2020). Importantly, Webster et al (2020: 290) suggest that reflective practice is a useful endeavour for people working in probation:…”
Section: Introductionmentioning
confidence: 99%
“…Here, Webster et al (2020) are describing action learning sets used in the Offender Personality Disordered (OPD) Pathway which were part of the original SEEDS programme in 2010. SEEDS2, which began in 2018, was developed by the Effective Probation Practice team in the National Probation Service and is intended to reintroduce the centrality of serviceuser engagement and upskilling probation staff.…”
Section: Introductionmentioning
confidence: 99%
“…Future research should further explore the reflective nature of the PICS and how it benefits the OMs in more ways than directly informing their working practices as was found in this research and recently in the work of Webster et al (2020). In addition, the effectiveness of the PICS in relation to the aims of the service could be further explored using quantitative methods of analyses.…”
Section: Limitations and Future Researchmentioning
confidence: 87%
“…Indeed, reflective practices have recently been found to be the most important aspect of the OPD pathway. Webster et al (2020) investigated the effectiveness of specific group reflective practice sessions, offered within the North and South Tyne clusters of the NPS. They found that the reflective sessions were extremely beneficial to the OMs in a number of ways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation